Manifestaciones orales en pacientes con COVID 19. Scoping Review (2022)
Introduction: In December 2019, a new virus called SARS-CoV2 emerged, its rapid spread worldwide generated a public health emergency, declared a pandemic; During the study of the disease, characteristic signs and symptoms such as dysgeusia, anosmia and xerostomia are identified; It is evident that at the level of the oral cavity manifestations and / or lesions occur during the period of infection. Objective: To map oral manifestations in databases such as Science Direct, Web of Science, Scopus and PubMed in patients diagnosed with COVID 19. Methodology: a review of articles published in databases (Pubmed, Web of Science and Scopus, Science Direct) since 2020 was conducted. Articles providing information on oral manifestations in patients with COVID-19, published from 2020 to date, were included; the Rayyan program for the selection and filtering of the extracted articles to perform a full text analysis was used. Results: 1437 articles were obtained, of which 1291 were excluded since they did not report on the topic of study, 58 duplicates of 146 were eliminated; 88 articles were retrieved for screening, after reading in full text 67 were excluded, finally obtaining 21 articles for this study. Conclusions: The structures that make up the oral cavity are a target organ for the anchoring of the SARS CoV2 virus due to the presence of ACE2 receptors along its extension, allowing the appearance of various manifestations and lesions, the knowledge of these is of utmost relevance for dental practice, which allows the clinician to give a timely diagnosis and ideal treatment; in the same way these manifestations and oral lesions during the Covid 19 infection requires more in-depth clinical research, which 15 allows establishing the existence of a direct relationship between the oral manifestations found and the SARS CoV2 virus. Key words: Oral manifestations, patients, Covid 19 infection.